Paul Gladue interview - Gladue, Paul; Starr, David (Canadian Plains Research Centre, 1975)
11 p. transcript of an interview with Mr. Paul Gladue, conducted by David Starr on November 14, 1975. Tape number IH-280, transcript disc 30. Mr. Paul Gladue, aged 75, describes the area of land covered by a trapper; the traditional lifestyle in northern Alberta; and work in Fort McMurray supplying wood to river steamboats. Other no